Analysis of Daily Mixed Language Conversation in Assisting the Sixth Semester Students’ of English Education Department Speaking Skills at Universitas Muslim Nusantara Al-Washliyah Medan - Violanda Ajeng Pachira; Rini Fadhilah Putri (Medan Resource Center, 2023)
In everyday life, people sometimes communicate with other people with mixed language and also as nowadays trend in social. There are words in English that commonly used in our daily conversation as Indonesian people to make the sentences clear and easy to be understood. This study aims to analyze the improvement of speaking skills through the habit of mixing languages in daily communication and conversation activities. The purpose of this research is to explain about the effect of mixed language in improving students' speaking skills and increasing their self-confidence. The researcher uses observation and interview approach to do the data collection of the sixth semester student in English Education Department Universitas Muslim Nusantara Al Washliyah Medan. The respondents were five students of the sixth semester students in English English Education Department Universitas Muslim Nusantara Al Washliyah Medan.